Representasi Seorang Ibu Tunggal yang Gaya Komunikasi menjadi Kunci Dasar Hubungannya dengan Sang Anak Di Film “Susah Sinyal” - Angel, Valentina Kyrie; Winduwati, Septia (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
Film as a form of mass communication has a very important role in conveying messages to a wide audience. As a visual medium, film is able to combine audio and visual elements and through narrative, characters and visualization, film can create social or cultural representations and can influence people's opinions or behavior. In this research, the film being studied is entitled